Mitochondrial dynamics controls anti-tumour innate immunity by regulating CHIP-IRF1 axis stability - Gao, Zhengjun; Li, Yiyuan; Wang, Fei; Huang, Tao; Fan, Keqi; Zhang, Yu; Zhong, Jiangyan; Cao, Qian; Chao, Tong; Jia, Junling; Yang, Shuo; Zhang, Long; et al. (Nature communications, 2017)
Macrophages, dendritic cells and other innate immune cells are involved in inflammation and host defense against infection. Metabolic shifts in mitochondrial dynamics may be involved in Toll-like receptor agonist-mediated inflammatory responses and immune cell polarization. However, whether the mitochondrial morphology in myeloid immune cells affects anti-tumor immunity is unclear. Here we show that FAM73b, a mitochondrial outer membrane protein, has a pivotal function in Toll-like receptor-regulated mitochondrial morphology switching from fusion to fission. Switching to mitochondrial fission via ablation of Fam73b (also known as Miga2 ) promotes IL-12 production. In tumor-associated macrophages, this switch results in T-cell activation and enhances anti-tumor immunity. We also show that the mitochondrial morphology affects Parkin expression and its recruitment to mitochondria. Parkin controls the stability of the downstream CHIP–IRF1 axis through proteolysis. Our findings identify mechanisms associated with mitochondrial dynamics that control anti-tumor immune responses and that are potential targets for cancer immunotherapy. Macrophage metabolism controls differentiation and subsequent adaptive immune responses. Here the authors show that mitochondrial membrane protein Fam73b regulates TLR-mediated mitochondrial switching of fusion to fission to induce IL-12 production via accumulation of Parkin and stabilization of IRF1 in macrophages, resulting in control of anti-tumor immunity in mice.